A new lizard species of the Liolaemus kingii group (Squamata: Liolaemidae) from northwestern Chubut province (Argentina) - Sánchez, Kevin I.; Morando, Mariana; Avila, Luciano J. (Zootaxa, 2023)
We describe Liolaemus attenboroughi sp. nov., a lizard distributed in the northwestern Patagonian Steppe of Chubut province (Argentina) previously confused with L. kingii (Bell 1843). Recent studies based on molecular evidence supports its evolutionary independence. Here we provide a morphological diagnosis of this lineage, comparisons between three molecular species delimitation methods, and an updated phylogeny of the L. kingii group. Based on current knowledge of its distribution, this new species is allopatric with geographically close species of the L. kingii group.